2022
DOI: 10.31599/sasana.v8i1.1101
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Asas Proporsionalitas Dalam Perjanjian Waralaba (Franchise) Pada Suatu Hubungan Kontrak Bisnis

Abstract: Pada hakekatnya bisnis waralaba merupakan  bentuk usaha yang memasarkan barang atau jasa yang memiliki ciri khas tertentu dalam kegiatannya. Kegiatan waralaba itu sendiri di Indonesia diatur dala Peraturan Menteri Perdagangan Nomor 71 tahun 2019 Tentang Peneyelenggaraan Waralaba .Perjanjian waralaba yang dilakukan oleh kedua belah pihak yang melakukan perjanjian dalam suatu kontrak bisnis harus berlandaskan kepada itikad baik dan berlandaskan asas proporsionalitas, dalam pengertian bahwa perjanjian tersebut me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Franchising in the business world is considered a highly beneficial system, as evidenced by various national and international companies (Atmoko, 2022). The globalization of franchising began in the 1990s due to factors such as domestic market saturation and intense domestic competition (Alon et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Franchising in the business world is considered a highly beneficial system, as evidenced by various national and international companies (Atmoko, 2022). The globalization of franchising began in the 1990s due to factors such as domestic market saturation and intense domestic competition (Alon et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the parties were in a reciprocal relationship and had balanced achievements. This indicated that the principle of proportionality or balance emphasized both parties providing each other with equal rights, leading to the existence of a fair agreement (Atmoko, 2022).…”
Section: Trademark Troubles: Unmasking Legal Liabilities In Franchise...mentioning
confidence: 99%
“…Waralaba merupakan hak khusus yang dimiliki oleh orang perseorangan atau badan usaha terhadap sistem bisnis dengan ciri khas usaha dalam rangka memasarkan barang dan/atau jasa yang telah terbukti berhasil dan dapat dimanfaatkan dan/atau digunakan oleh pihak lain (Harnoko and Ratnawati 2015). Waralaba (Franchise) pada dasarnya adalah sebuah perjanjian mengenai metode pendistribusian barang dan jasa kepada konsumen.…”
Section: Hasil Dan Pembahasanunclassified